The Impact of Buyer Concentration–An Extension - LaFrance, Vincent A. (The Review of Economics and Statistics, 1979)
induced Unemployment in Canadian Journal of Economics 8 (May 1975), 174-191. Gujarati, Damodar, The Behaviour of Unemployment and Unfilled Vacancies: Great Britain, 1958-1971, Economic Journal 82 (Feb. 1972), 195-204. Hansen, Bent, Excess Demand, Unemployment, Vacancies, and Wages, Quarterly Journal of Economics 84 (Feb. 1970), 1-23. Meltz, Noah M., Information Requirements for Government Programs Directed toward the Labour Market (Ottawa: Economic Council of Canada, 1974). Perry, G. L., Changing Labor Markets and Inflation, Brookings Papers on Economic Activity (1970), 411448. Reid, Frank, Dummy Variables with a Transitional Phase, Canadian Journal of Economics 10 (May 1977), 326-329. Skolnik, M. L., and F. Siddiqui, The Paradox of Unemployment and Job Vacancies: Some Theories Confronted by Data, Relations Industrielles 31 (1976), 32-56. Wilton, D. A., Wage Determination Process in Canadian Manufacturing Industries, 1962-1975 (Ottawa: Labour Canada, 1977).